Work Environment, Work Stres, And Work Motivation Influence Organizational Commitment - abdul, Abdul Ngazis; Epsilandri Septyarini; Nala Tri Kusuma (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This study was conducted to examine the influence of work environment, work stress, and work motivation on organisational commitment at Permata Medika Kebumen General Hospital. This research uses quantitative methodology. The population size at Permata Medika Kebumen General Hospital was 300 employees and a sample of 75 employees was taken. The sampling method used is simple ramdom sampling, which is sampling that ensures each member of the population has the same opportunity to be selected as a sample and to determine the number of samples using the Slovin formula. The research results show that work environment, work stress, and work motivation have a significant positive effect on organisational commitment. Furthermore, these factors collectively affect organisational commitment positively. This research is expected to be a reference and improvement for Permata Medika Kebumen General Hospital in improving employee capabilities, making policies for employees so that employee commitment will increase and make Permata Medika Kebumen General Hospital able to obtain services to consumers so that organisational goals are achieved.